Origin of the Co uniaxial volume anisotropy of the fcc Co/Ni/Cu(001) system - Lauhoff, G; Bland, J; Lee, J; Langridge, S; Penfold, J (1999)
We studied layer selectively the magnetic moments on a Cu/9 Å Co/50 Å Ni/Cu/Si(001) and a Cu/50 Å Ni/Cu/Si(001) structure using polarized neutron reflection. The magnetic moments for the Cu/Co/Ni/Cu structure are 1.70±0.20 μB and 0.57±0.05μB for the Co and Ni, respectively, and within error the same as the relevant bulk magnetic moments at room temperature. For the Cu/Ni/Cu sample the magnetic moment per Ni atom of 0.53±0.03μB is only slightly lower than the bulk value. Within error the same magnetic moments are determined for a Cu/22 Å Co/11 Å Cu/53 Å Ni/Cu/Si(001) structure supporting the results on the Cu/Co/Ni/Cu(001) and Cu/Ni/Cu(001) structures. Using the magnetic moments values determined by polarized neutron reflection, we conclude that the uniaxial Co volume anisotropy for the Cu/Co/60 Å Ni/Cu(001) structures can be attributed to the Co shape anisotropy alone. ©1999 The American Physical Society.